Impact of Fast Foods and Snacks upon Adolescents' BMI at Secondary Schools in Baghdad City - Saleh, Buthainah; Ma΄ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2015)
Objective: The study aimed to identify the adolescents' fast foods and snacks, and find out the relationship between fastfood, snacks and adolescents' demographic data (gender and Body Mass Index). Methodology: A descriptive studywas conducted on impact of fast foods and snacks upon adolescents' Body Mass Index in secondary schools at Baghdadcity, starting from 20th of April 2013 to the end of October 2014. Non- probability (purposive) sample of 1254adolescents were chosen from secondary schools of both sides of Al-Karkh and Al-Russafa sectors. Data was collectedthrough a specially constructed questionnaire format include (12) items multiple choice questions. The validity of thequestionnaire was determined through a panel of experts related to the field of the study, and the reliability through apilot study. The data were analyzed through the application of descriptive statistical analysis frequency, & percentages,and inferential statistical analysis, chi-square, are used.Results: The study results revealed that more than one third and half of the sample daily take soft drink, sometimeseating cake and other crackers, chocolate or cocoa, ice cream, sweets, chips, artificial fruit juice, milk and dairyproducts, beans nuts, and drink tea or coffee respectively. The study sample have more than one third (37.4%)sometimes eat fast food in their home, and (38.1%) seldom eat fast food from out. Eat the snacks food highlysignificant association with adolescents' gender but eat the fast foods not significant association with their gender. Thereis highly significant association between eat the snacks and fast foods in home with their Body Mass Index but eat thefast foods out home not significant association with their Body Mass Index.Recommendation: The study recommended that Ministry Of Health should activate the healthy eating snacks and fastfoods program within school health service programs, and Ministry of Education should be involved their teachers inthe healthy eating programs & training them on the healthy eating strategies.